Fosseal - a sealer mechanism for food waste management - Abdul Rahman, Julaila; Ramdan, Nuur Hafizah; Kamaruddin, Zumahiran (Kulliyyah of Architecture & Environmental Design, International Islamic University Malaysia, 2019)
This research aims to identify the behavior of household towards food waste management in the home kitchen and to propose a better way of food waste management method by developing a product. A total of 32 person (24 female and 8 male) were selected for a survey study. Two instruments were developed to collect data; first instrument was photography to show the real situation of waste management in one kitchen and second instrument was a survey questionnaire. The findings indicated that most of the respondents aware of Waste Separate Programme and has tried to separate their home waste. This study also figured out behavior of household on their home food waste management. Most of respondents tie the plastic that contain rubbish before throw it into the Green Bin provided by their authority. The user prefers using small waste bin with a lid to help to prevent from bad smell comes from the waste bin and from insects and other animals. FOSSEAL is a new eco-friendly product that has a potential to improve the waste management at home as well as in formal institution i.e. hospital, school and offices.